Low incidence of failure after proximal biceps tenodesis with unicortical suture button - Cook, Jay B. (J Orthop, 2017)
PURPOSE: Recent interest in suture button fixation has developed with regard to proximal biceps tenodesis fixation. Biomechanical studies have demonstrated viability of a unicortical suture button technique in vitro. Despite this, no clinical data has been reported to validate the biomechanical data. The purpose of this study is to report on complication and failure rates in the early postoperative period after bicep tenodesis with a unicortical suture button. METHODS: A retrospective review was performed of all biceps tenodesis performed at our institution over a 36-month period using a unicortical suture button for fixation. All included patients had a minimum 12 weeks follow up. Failures were defined as complete loss of fixation, change in biceps contour during the early postoperative period, acute pain at the tenodesis site, or acute loss of supination strength. RESULTS: 145 of 166 biceps tenodesis procedures performed by the 4 surgeons at our institution met inclusion criteria. 80.1% of the patients were active duty military at the time of surgery. The average age was 38.2 years. There were 7 total complications (4.8%), including one failure (0.7%) requiring revision. CONCLUSION: Failure and complication rates in the early postoperative period using a unicortical suture button for biceps tenodesis fixation are consistent with other reported techniques. This study adds clinical data to the existing biomechanical reports that this technique is strong enough to provide stable fixation of the biceps tendon to allow healing of the tendon to the humerus.